2016
DOI: 10.3389/fmicb.2016.00993
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Bacterial Volatile 2,3-Butanediol on Bacillus subtilis Rhizosphere Robustness

Abstract: Volatile compounds, such as short chain alcohols, acetoin, and 2,3-butanediol, produced by certain strains of root-associated bacteria (rhizobacteria) elicit induced systemic resistance in plants. The effects of bacterial volatile compounds (BVCs) on plant and fungal growth have been extensively studied; however, the impact of bacterial BVCs on bacterial growth remains poorly understood. In this study the effects of a well-characterized bacterial volatile, 2,3-butanediol, produced by the rhizobacterium Bacillu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 59 publications
1
63
0
Order By: Relevance
“…). These volatile organic compounds are known as plant‐growth promoting factors (Ryu et al, ) and 2,3‐butanediol has been shown to induce systemic resistance (Han et al, ) and modulates root exudation (Yi et al, ). Every strain also possesses the pyrroloquinoline quinone (PQQ) biosynthetic operon pqqFABCDEF (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…). These volatile organic compounds are known as plant‐growth promoting factors (Ryu et al, ) and 2,3‐butanediol has been shown to induce systemic resistance (Han et al, ) and modulates root exudation (Yi et al, ). Every strain also possesses the pyrroloquinoline quinone (PQQ) biosynthetic operon pqqFABCDEF (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Ryu’s group studied rhizosphere colonization of pepper, using the wild-type 2,3-butanediol producer B. subtilis 168, its null mutant, and a 2,3-butanediol-overproducing derivative. The results showed that a higher level of 2,3-butanediol production correlates with improved rhizosphere competence of B. subtilis itself and that 2,3-butanediol production by B. subtilis suppresses the growth of the saprophytic fungus Trichoderma in the rhizosphere 74 . Furthermore, growth experiments were carried out in exudates of roots pre-treated with the 2,3-butanediol-overproducing strain.…”
Section: War In the Rhizospherementioning
confidence: 97%
“…The same pre-treatment also inhibited the growth of the soil-borne bacterial pathogen R. solanacearum but enhanced the growth of the saprophytic biocontrol bacterium P. protegens Pf-5. Apparently, 2,3-butanediol alters the root exudate composition 74 .…”
Section: War In the Rhizospherementioning
confidence: 99%
See 1 more Smart Citation
“…Microbiota that suppress plant disease typically accumulate in soil after a response to plant stress, such as disease occurrence, in the field. During disease development, plants secrete root exudates that recruit disease-suppressive microbiota (Yi et al, 2016). Such microbiota can accumulate even after diseased plants are removed from the field.…”
Section: Plant Recognition and Microbiota Reshapingmentioning
confidence: 99%